GUIDANCE AND COUNSELING TEACHERS IN FOSTERING STUDENTS' DISCIPLINARY ATTITUDES IN JUNIOR HIGH SCHOOLS - Putri, Fyni Afrilyani; Yanto, Yanto; Ferdiansyah, Muhammad (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
The issue of student discipline becomes very important for the learning process at school. If students are not disciplined with all the school rules and regulations, the learning process will be disrupted, becoming uncomfortable and disorganized, which in turn encourages students to commit violations. This research aims to analyze the role of Guidance and Counseling teachers in instilling students' discipline, as well as to describe the strategies used by Guidance and Counseling teachers in fostering students' discipline. The research method used in this study is qualitative research. There are four methods of data collection techniques, namely through observation, interviews, the distribution of questionnaires in the form of question lists, and through assessment tests that involve analysis. The results of the field research findings revealed that the role of the guidance counselor in instilling discipline among students at SMP has been implemented quite well.